Comparison in Bone Density Changes for Two Different Designs in Treatment of Mandibular Bilateral Free End Saddle with Osseointegrated Implants - Sabra, Seham Ali El-Sayed; Fekry, Gehan; Agamy, Emad (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of this study is to evaluate two different designs in mandibular bilateral free end saddle cases with the use of osseointegrated implants. The designs evaluated were OT-strategy extracoronal attachment and bar attachment. Radiographic evaluation was carried out for implants and natural abutment in terms of bone density. MATERIALS AND METHODS: This study was conducted on 10 patients with bilateral distal extension area with missing molars bilaterally; the patients were divided into two groups after implant insertion on the second molar area. Group I: Patients received extracoronal attachment distal to the last natural abutment teeth with the construction of metallic removable partial denture (RPD). Group II: Patients received bar attachment with the construction of metallic RPD. Both groups have the maxillary arch edentulous with the construction of complete maxillary dentures within our study. Radiographic evaluation for bone density was done for both groups at the time of prosthesis insertion, 3, 6, and 9 months later. A comparison between the two groups regarding each follow-up period was performed by an independent t-test. RESULTS: Although there were some differences between both designs in the 1st-time intervals, generally, there were no significant differences between the two designs all over the 3-time intervals. CONCLUSION: From the results of this study, it was concluded that: Although there were no significant differences between both designs, bar-attachment showed better results which should be confirmed with more future researches.